ORGANIZATIONAL AND ECONOMIC BASES OF CONSTRUCTION AND RECONSTRUCTION OF OBJECTS OF TRANSPORT DESTINATION OF HIGH-SPEED RAILWAY LINES ORGANIZATION - Volkov, Ye. I.; Chashyn, D. Yu.; Dotsenko, R. O. (Science and Transport Progress, 2006)
The goal of the work is improvement of methodological and methodical principles of development of the estimation and planning systems, which is modelled with the use of system approach methods, as an integral part of the organizational and economical preparation to the construction of transport facilities and high-speed railway lines.